Positive electrode material and preparation method thereof, battery and electric device

By using a double-layer cladding structure on the positive electrode material of the battery and using oxides, sulfides or halide solid electrolytes as the cladding material, the problem of poor interface compatibility between the positive electrode material and the solid electrolyte is solved, and the energy of the battery is significantly improved Density and cyclic stability.

CN119447231APending Publication Date: 2025-02-14GUANGZHOU AUTOMOBILE GROUP CO LTD
View PDF 0 Cites 9 Cited by

Patent Information

Application Number
CN202411496161.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The poor interface compatibility between the existing battery positive electrode material and the solid electrolyte affects the electrochemical performance of the battery.

Method used

The positive electrode material adopts a double-layer clad structure, wherein the core is composed of materials such as nickel-cobalt-lithium manganate. The first clad layer includes an oxide, sulfide or halide solid electrolyte, and the second clad layer also includes a halide solid electrolyte. , a cladding layer is formed by agitating treatment or spraying treatment.

Benefits of technology

The interface compatibility between the positive electrode and the electrolyte layer is improved, and the energy density and cycle stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447231A_ABST
    Figure CN119447231A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method thereof, a battery and a power utilization device. The positive electrode material comprises an inner core; the first coating layer comprises a first coating material, and the first coating material comprises at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte and a polymer composite solid electrolyte; the first coating layer coats the inner core, the second coating layer coats the inner core, the first coating layer coats the second coating layer, the second coating layer comprises a second coating material, and the second coating material comprises a halide solid electrolyte. The coating layer plays a certain role in isolating the material of the inner core from the external environment, and the situation that the material in the inner core has side reaction with external substances or the property of the material is changed due to other reasons is reduced. Therefore, the performance stability of the positive electrode material is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery materials, and in particular, to positive electrode materials and preparation methods thereof, batteries, and electrical devices. Background Art

[0002] Battery performance depends largely on the selection and structure of cathode materials. Some batteries have poor interface compatibility between cathode materials and electrolyte layers, which affects the electrochemical performance of the battery. Summary of the invention

[0003] In the first aspect of the present application, the present application proposes a positive electrode material, comprising: a core; a first coating layer, the first coating layer comprising a first coating material, the first coating material comprising at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer composite solid electrolyte; a second coating layer, the second coating layer coating the core, the first coating layer coating the second coating layer, the second coating layer comprising a second coating material, and the second coating material comprising a halide solid electrolyte.

[0004] The positive electrode material of the present application has two coating layers, and both the coating layer and the core have good stability, which effectively improves the interface compatibility between the positive electrode and the electrolyte layer.

[0005] In some embodiments, the core includes at least one of lithium nickel cobalt manganese oxide, lithium iron manganese phosphate, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese rich base, lithium nickel manganese oxide, and lithium vanadium phosphate.

[0006] In some embodiments, the core comprises LiFePO4, LiFe x0 Mn y0 PO4, where x0+y0=1, Li3V2(PO4)3, LiVOPO4, LiNi x Co y Al z O2, where 0.7≤x≤0.85, 0.1≤y≤0.2, 0.05≤z≤0.1, LiNi 1-x’-y’ Mn x’ Co y’ O2, where 0.01≤x'≤0.95, 0.01≤y'≤0.95, LiCoO2, LiNiO2, LiMn2O4, LiNi 0.5 Mn 1.5 O. Li 1.2 Ni 0.2 Mn 0.6 O2、Li 1.2 Co 0.4 Mn 0.4O2、x1Li2MnO3·(1-x1)LiNi 0.5 Mn 1.5 O4, where 0.05≤x1≤0.95, x2Li2MnO3·(1-x2)LiNi a2 Co b2 Mn c2 O2, wherein 0.05≤x2≤0.95, 0≤b2≤0.5, a2+b2+c2=1, at least one of the following. The aforementioned core material can be used as a positive electrode material for a solid-state lithium-ion battery, and has good structural stability and high gram capacity.

[0007] In some embodiments, the room temperature ionic conductivity of the first coating material is ≥ 1E-4 S / cm.

[0008] In some embodiments, the D50 of the inner core is 0.5 μm-20 μm.

[0009] In some embodiments, the first coating material has an oxidation onset potential greater than or equal to 4.0 V for lithium.

[0010] In some embodiments, the D50 of the cathode material core is 1.0 μm-10 μm, and the BET is 5 μm. 2 / g-30m 2 / g.

[0011] In some embodiments, the thickness of the first cladding layer is 1 nm-50 nm.

[0012] In some embodiments, the thickness of the second cladding layer is 1 nm-50 nm.

[0013] In some embodiments, the second coating material includes Li2MnCl4, Li2ZnCl4, Li2ZrOCl4, LiYbF4, LiAlF4, Li3YCl6, Li3InCl6, Li3InCl 5.5 F 0.5 、Li3TaCl6、Li 0.388 Ta 0.238 La 0.475 At least one of Cl3, Li6CoCl8.

[0014] In some embodiments, the BET (specific surface area) of the core is 0.5 m 2 / g-50m 2 / g.

[0015] In some embodiments, the thickness of the first coating layer is 2 nm-10 nm.

[0016] In some embodiments, the oxide solid electrolyte includes at least one of a sodium super ion conductor structure material (NASICON), a perovskite structure material, an inverse perovskite structure material, a sulfide lithium ion conductor structure (LISICON) and a garnet structure material. Thus, the aforementioned oxide solid electrolyte satisfies the room temperature ionic conductivity greater than or equal to 1E -4 S / cm, and the oxidation starting potential of the material to lithium is greater than or equal to 4.0V.

[0017] In some embodiments, the sulfide solid electrolyte includes Li2S-P2S5, Li 10 GeP2S 12 、Li3PS4、Li 6- x3 PS 5-x3 Cl 1+x3 , where 0≤x3≤0.8.

[0018] In some embodiments, the molecular formula of the halide solid electrolyte is Li a4 (M b4 )X c4 X' d4 , wherein M includes at least one of Ga, Y, In, Mg, Sr, Sc, Sn, Pb, Ti, Zr, Hf, Nb, Ta, W, Fe, Ru, Al, and lanthanide metal elements, X includes at least one of halogen elements, X' includes at least one of halide ions, N ions, oxygen-containing anion groups, and pseudohalide anions, and the oxygen-containing anion groups include O 2- , S 2- , CN - 、CO3 2- PO4 3- 、P2O7 4- 、SO4 2- At least one of the pseudohalide anions includes SCN - PF 6- NH 2- , AlF 4- , or BF 4- At least one of the following, wherein 0.5≤a4≤5, 0.2≤b4≤4, c4+d4=a4+b4ε, wherein ε is the weighted average valence of the M element.

[0019] In some embodiments, the polymer composite solid electrolyte includes a polymer and a lithium salt, wherein the polymer includes at least one of polyethylene oxide, polyacrylate, polyvinylidene fluoride, hexafluoropropylene copolymer, polysiloxane, polyethylene glycol, sodium polystyrene sulfonate, polyvinyl cyanide, polysulfone, and polyether sulfone, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluoroantimonate, lithium bis(trifluoromethanesulfonate imide), lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium iodide, lithium magnesium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.

[0020] In some embodiments, the mass of the lithium salt in the polymer composite solid electrolyte accounts for 5 wt % to 100 wt % of the mass of the polymer.

[0021] In some embodiments, the mass of the lithium salt in the polymer composite solid electrolyte accounts for 10 wt%-20 wt% of the mass of the polymer.

[0022] In some embodiments, the thickness of the first cladding layer is 3 nm-6 nm.

[0023] In some embodiments, the oxide solid electrolyte includes Li 3x5 La 2 / 3-x5 TiO, 0≤x5≤0.16, Li 1+x6 Al x6 Ti 2-x6 (PO4)3, where 0≤x6≤0.5, Li 1+x7 Al x7 Ge 2-x7 (PO4)3, where 0≤x7≤0.5, Li7La3Zr2O 12 In some embodiments, the sulfide solid electrolyte includes at least one of Li2SP2S5 and Li6PS5Cl.

[0024] In some embodiments, the halide solid electrolyte includes Li2MnCl4, Li2ZnCl4, Li2ZrOCl4, LiYbF4, LiAlF4, Li3YCl6, Li3InCl6, Li3InCl 5.5 F 0.5 、Li3TaCl6、Li 0.388 Ta 0.238 La 0.475 At least one of Cl3, Li6CoCl8.

[0025] In some embodiments, the polymer composite solid electrolyte includes at least one of polyethylene oxide, hexafluoropropylene copolymer, and polyvinyl cyanide.

[0026] In the second aspect of the present application, the present application proposes a method for preparing a positive electrode material: in a protective atmosphere, the inner core and the first coating material are subjected to a first stirring treatment to obtain a positive electrode material, wherein the first coating material includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer composite solid electrolyte; the protective atmosphere includes at least one of nitrogen and an inert gas.

[0027] The method for preparing positive electrode materials proposed in the present application uses a coating material with good physical and chemical stability and surface coating properties, and a coating layer of a certain thickness can be formed on the surface of the inner core through stirring treatment, thereby achieving surface optimization of the inner core material.

[0028] In some embodiments, the method further comprises, before the first stirring process, subjecting the core to a second stirring process with a second coating material, thereby achieving more than one layer of surface coating process on the surface of the core.

[0029] In the third aspect of the present application, the present application proposes a method for preparing a positive electrode material: spraying a core precursor, wherein the sprayed slurry includes a coating material and a solvent to obtain a preformed positive electrode material; and sintering the preformed positive electrode material to obtain the positive electrode material.

[0030] The coating material in the present application can be prepared into a slurry with good dispersibility and appropriate concentration, which is suitable for spraying treatment, can form a relatively uniform coating layer on the surface of the inner core, and can be solidified by sintering treatment.

[0031] In some embodiments, the method further comprises: performing a first spraying treatment and a pre-sintering treatment on the core precursor in sequence, wherein the slurry of the first spraying treatment includes a second coating material; performing a second spraying treatment on the pre-sintered core precursor, wherein the slurry of the second spraying treatment includes the first coating material, so as to obtain the preformed positive electrode material. Thus, a multilayer structure in which a plurality of coating layers are coated on the core is realized.

[0032] In some embodiments, the pre-sintering temperature is 200° C.-600° C., and the pre-sintering time is 1 h-24 h.

[0033] In some embodiments, the sintering temperature is 800° C.-1200° C., and the sintering time is 1 h-48 h.

[0034] In some embodiments, the solvent includes at least one of ethyl acetate, butyl butyrate, acetonitrile, acetone, toluene, xylene, ether, heptane, decane, hexane, n-heptane, chloroform, tetrahydrofuran, ethanol, butanol, N,N-dimethylacetamide, N,N-dimethylformamide, 2,2,2-trifluoro-N,N-dimethylformamide, and N-methylpyrrolidone.

[0035] In a fourth aspect of the present application, the present application proposes a battery, wherein the battery comprises the positive electrode material proposed in the present application.

[0036] In a fifth aspect of the present application, the present application proposes an electrical device, wherein the electrical device comprises the battery proposed in the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0038] Figure 1 This is a schematic diagram of a positive electrode material in one embodiment of the present application;

[0039] Figure 2 This is a schematic diagram of the positive electrode material in one embodiment of the present application.

[0040] Description of reference numerals:

[0041] Core 01; second cladding layer 11; first cladding layer 12. DETAILED DESCRIPTION

[0042] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0043] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0044] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0045] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0046] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0047] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0048] With the rapid development of mobile devices, electric vehicles and energy storage systems, the demand for high-safety and high-energy-density batteries is growing. Solid-state lithium-ion batteries (SSLBs) energy storage technology has better safety and higher energy density. Solid-state electrolytes (SSEs) have the advantages of being non-flammable and highly chemically stable, and can replace liquid electrolytes in traditional lithium-ion batteries, thereby eliminating the risks of leakage, volatilization and thermal runaway caused by liquid electrolytes. However, the application of solid-state lithium-ion batteries still faces many challenges, such as the interface compatibility problem between the cathode material and the solid-state electrolyte.

[0049] When positive electrode materials, such as lithium cobalt oxide, ternary materials, lithium manganese-rich positive electrode materials and lithium iron phosphate, are used in combination with solid electrolytes, side reactions or defects will occur at the interface between the two, thereby affecting the stability of the positive electrode materials. For example, chemical side reactions may occur between the positive electrode material and the solid electrolyte during the charge and discharge process, resulting in decreased interface stability and performance degradation, and reduced ion transfer efficiency caused by the gaps between the interfaces. In order to solve the above problems, the surface properties of the positive electrode material can be improved to improve its interfacial stability with the solid electrolyte. In this application, the chemical and physical matching between the positive electrode material and the solid electrolyte is optimized by improving the surface and structure of the positive electrode material to improve the energy density and cycle stability of the battery.

[0050] In the first aspect of the present application, the present application proposes a positive electrode material, comprising: a core; a first coating layer, the first coating layer comprising a first coating material, the first coating material comprising at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer composite solid electrolyte; a second coating layer, the second coating layer coating the core, the first coating layer coating the second coating layer, the second coating layer comprising a second coating material, and the second coating material comprising a halide solid electrolyte.

[0051] The positive electrode material of the present application comprises a core and a first coating layer, Figure 1 , the first coating layer plays a role in isolating the core material from the external environment. The solid electrolyte material in the first coating layer has good structural stability and high ionic conductivity. The first coating layer forms a protective interface outside the core, and through the isolation effect, reduces the side reactions between the core material and external substances or changes in properties due to other reasons, thereby maintaining the stability of the performance of the positive electrode material. Due to its own good electrical properties, it can protect the core while maintaining a high electrical conductivity to improve the interface compatibility between the core material and the solid electrolyte in the solid-state battery. Further includes a second coating layer, the second coating layer is located between the first coating layer and the core, the second coating layer includes a second coating material, and the second coating material includes a halide solid electrolyte. Reference Figure 2 , within the aforementioned thickness range, the second coating layer can better wrap the inner core to form interface protection.

[0052] In some embodiments, the core includes at least one of lithium nickel cobalt manganese oxide, lithium iron manganese phosphate, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese rich base, lithium nickel manganese oxide, and lithium vanadium phosphate.

[0053] In some embodiments, the core comprises LiFePO4, LiFe x0 Mn y0PO4, where x0+y0=1, Li3V2(PO4)3, LiVOPO4, LiNi x Co y Al z O2, where 0.7≤x≤0.85, 0.1≤y≤0.2, 0.05≤z≤0.1, LiNi 1-x’-y’ Mn x’ Co y’ O2, where 0.01≤x'≤0.95, 0.01≤y'≤0.95, LiCoO2, LiNiO2, LiMn2O4, LiNi 0.5 Mn 1.5 O. Li 1.2 Ni 0.2 Mn 0.6 O2、Li 1.2 Co 0.4 Mn 0.4 O2、x1Li2MnO3·(1-x1)LiNi 0.5 Mn 1.5 O4, where 0.05≤x1≤0.95, x2Li2MnO3·(1-x2)LiNi a2 Co b2 Mn c2 O2, wherein 0.05≤x2≤0.95, 0≤b2≤0.5, a2+b2+c2=1, at least one of the following.

[0054] In some embodiments, the room temperature ionic conductivity of the first coating material is ≥ 1E -4 S / cm.

[0055] In some embodiments, the D50 of the inner core is 0.5 μm-20 μm.

[0056] In some embodiments, the first coating material has an oxidation onset potential greater than or equal to 4.0 V for lithium.

[0057] In some embodiments, the D50 of the cathode material core is 1.0 μm-10 μm, and the BET is 5 μm. 2 / g-30m 2 / g.

[0058] In some embodiments, the thickness of the first coating layer is 1 nm-50 nm. Within the aforementioned thickness range, the first coating layer can form a relatively complete outer layer to protect the material of the inner core.

[0059] In some embodiments, the thickness of the second cladding layer is 1 nm-50 nm.

[0060] In some embodiments, the second coating material includes Li2MnCl4, Li2ZnCl4, Li2ZrOCl4, LiYbF4, LiAlF4, Li3YCl6, Li3InCl6, Li3InCl 5.5 F 0.5 、Li3TaCl6、Li 0.388 Ta 0.238 La 0.475 At least one of Cl3, Li6CoCl8.

[0061] In some embodiments, the core comprises LiNi 0.5 Co 0.3 Mn 0.2 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 A1 0.05 O2, LiCoO2, LiNi 0.5 Co 0.2 Mn 0.2 A1 0.1 O2、LiCo 0.5 Ni 0.5 At least one of O2 and LiNiO.

[0062] Therefore, the aforementioned core material has better structural stability and higher gram capacity.

[0063] In some embodiments, the BET (specific surface area) of the core is 0.5 m 2 / g-50m 2 / g.

[0064] In some embodiments, the thickness of the first coating layer is 2 nm-10 nm.

[0065] In some embodiments, the oxide solid electrolyte includes at least one of a sodium superion conductor structure material, a perovskite structure material, an inverse perovskite structure material, a sulfur-substituted lithium ion conductor structure, and a garnet structure material.

[0066] In some embodiments, the sulfide solid electrolyte includes Li2S-P2S5, Li 10 GeP2S 12 、Li3PS4、Li 6- x3 PS 5-x3 Cl 1+x3, where 0≤x3≤0.8.

[0067] Sulfide solid electrolytes have high ion conductivity, which is conducive to the free movement of lithium ions. At the same time, the bulk modulus of sulfide solid electrolytes is low. In the process of preparing the first coating layer, the deformation of the sulfide solid electrolyte is more controllable, which is conducive to forming a structurally stable coating layer structure.

[0068] In some embodiments, the molecular formula of the halide solid electrolyte is Li a4 (M b4 )X c4 X' d4 , wherein M includes at least one of Ga, Y, In, Mg, Sr, Sc, Sn, Pb, Ti, Zr, Hf, Nb, Ta, W, Fe, Ru, Al, and lanthanide metal elements, X includes at least one of halogen elements, X' includes at least one of halide ions, N ions, oxygen-containing anion groups, and pseudohalide anions, and the oxygen-containing anion groups include O 2- , S 2- , CN - 、CO3 2- PO4 3- 、P2O7 4- 、SO4 2- At least one of the pseudohalide anions includes SCN - PF 6- NH 2- , AlF 4- , or BF 4- At least one of the following, wherein 0.5≤a4≤5, 0.2≤b4≤4, c4+d4=a4+b4ε, wherein ε is the weighted average valence of the M element.

[0069] The halide solid electrolyte has high ionic conductivity, which is conducive to the free movement of lithium ions. At the same time, the halide solid electrolyte has strong oxidation resistance and low bulk modulus. Therefore, the physical and chemical structure of the first coating layer prepared by the halide solid electrolyte is relatively stable. The prepared positive electrode material coated with the first coating layer has good stability.

[0070] In some embodiments, the polymer composite solid electrolyte includes a polymer and a lithium salt, wherein the polymer includes at least one of polyethylene oxide, polyacrylate, polyvinylidene fluoride, hexafluoropropylene copolymer, polysiloxane, polyethylene glycol, sodium polystyrene sulfonate, polyvinyl cyanide, polysulfone, and polyether sulfone, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluoroantimonate, lithium bis(trifluoromethanesulfonate imide), lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium iodide, lithium magnesium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.

[0071] The polymer composite solid electrolyte includes a polymer and a lithium salt, and has high ionic conductivity. In addition, the polymer composite solid electrolyte has good processing performance brought by the polymer. Different polymers can adapt to different processing equipment and processing conditions, and have wider industrial applicability.

[0072] In some embodiments, the mass of the lithium salt in the polymer composite solid electrolyte accounts for 5 wt % to 100 wt % of the mass of the polymer.

[0073] In some embodiments, the mass of the lithium salt in the polymer composite solid electrolyte accounts for 10 wt%-20 wt% of the mass of the polymer.

[0074] In some embodiments, the thickness of the first coating layer is 3nm-6nm. Within the aforementioned thickness range, the first coating layer has good ionic conductivity. Lithium ions can pass through the first coating layer relatively freely and move from the positive electrode to the negative electrode inside the battery. Moreover, within the aforementioned thickness range, the movement of electrons is also relatively free, and electrons can move through quantum tunneling.

[0075] In some embodiments, the oxide solid electrolyte includes Li 3x5 La 2 / 3-x5 TiO, 0≤x5≤0.16, Li 1+x6 Al x6 Ti 2-x6 (PO4)3, where 0≤x6≤0.5, Li 1+x7 Al x7 Ge 2-x7 (PO4)3, where 0≤x7≤0.5, Li7La3Zr2O 12 Thus, the oxide solid electrolyte has good electrical conductivity, and the oxide solid electrolyte has high chemical stability, the first coating layer prepared therefrom has high stability, and the positive electrode material having the first coating layer also has high stability.

[0076] In some embodiments, the sulfide solid electrolyte includes at least one of Li2S-P2S5 and Li6PS5Cl.

[0077] The ionic conductivity of the sulfide solid electrolyte is greater than or equal to 1e -3 S / cm, a positive electrode material having a first coating layer prepared therefrom, wherein lithium ions can pass through the first coating layer relatively freely. In addition, the aforementioned material is easy to obtain, which is conducive to reducing production costs. Under the protection of the first coating layer, the positive electrode material has a relatively stable interface stability to the solid electrolyte.

[0078] In some embodiments, the halide solid electrolyte includes Li2MnCl4, Li2ZnCl4, Li2ZrOCl4, LiYbF4, LiAlF4, Li3YCl6, Li3InCl6, Li3InCl 5.5 F 0.5 、Li3TaCl6、Li 0.388 Ta 0.238 La 0.475 At least one of Cl3, Li6CoCl8.

[0079] The ionic conductivity of the aforementioned halide solid electrolyte is greater than or equal to 0.5×10 -3 S / cm, which is conducive to the free movement of lithium ions. At the same time, the aforementioned sulfide solid electrolyte has a low bulk modulus and low hardness. In the process of preparing the first coating layer, the deformation of the sulfide solid electrolyte is more controllable and easy to process into a film structure, which is conducive to forming a structurally stable coating layer structure. Under the protection of the first coating layer, the positive electrode material has a relatively stable interface stability to the solid electrolyte.

[0080] In some embodiments, the polymer composite solid electrolyte includes at least one of polyethylene oxide, hexafluoropropylene copolymer, and polyvinyl cyanide. Therefore, because the aforementioned polymer composite solid electrolyte has excellent processing performance and conductivity, lithium ions in the prepared positive electrode material having the first coating layer can move freely, and the positive electrode material has a relatively stable interface stability to the solid electrolyte under the protection of the first coating layer.

[0081] In some embodiments, a ratio of a thickness of the second cladding layer to a thickness of the first cladding layer is (5:1)-(1:5).

[0082] In the second aspect of the present application, the present application proposes a method for preparing a positive electrode material, comprising: in a protective atmosphere, subjecting the inner core and the first coating material to a first stirring treatment to obtain a positive electrode material, wherein the first coating material comprises at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer composite solid electrolyte; and the protective atmosphere comprises at least one of nitrogen and an inert gas.

[0083] The method for preparing positive electrode materials proposed in the present application uses a first coating material with good physical and chemical stability and surface coating properties. Under the action of a protective atmosphere, side reactions between the core material and the first coating material or other substances in the preparation environment can be avoided. The stirring treatment allows the first coating material to form a coating layer of a certain thickness on the surface of the core through mechanical fusion, thereby achieving surface protection of the core and optimization of the surface structure.

[0084] In some embodiments, the stirring treatment device can be a blade mixer, a high-energy planetary mill, a magnetic stirrer, or a mechanical high-speed differential mixer.

[0085] In some embodiments, the stirring treatment device may be a high-energy planetary mill or a mechanical high-speed differential mixer.

[0086] In some embodiments, the protective atmosphere is argon gas, and the purity of argon gas is ≥99%.

[0087] In some embodiments, the vacuum degree of the protective atmosphere is -99.0 kPa to -86.0 kPa.

[0088] In some embodiments, the vacuum degree of the protective atmosphere is -99.0 kPa to -90.0 kPa.

[0089] In some embodiments, the method further comprises subjecting the core and the second coating material to a second stirring process before the first stirring process, thereby forming a second coating layer on the surface of the core, and then forming a first coating layer on a side of the second coating layer away from the core.

[0090] In some embodiments, the first stirring process and the second stirring process may include a low-speed stirring process and a high-speed stirring process, wherein the rotation speed of the low-speed stirring process is 200rpm-400rpm, and the stirring time of the low-speed stirring process is 0.5h-2h; the rotation speed of the high-speed stirring process is 500rpm-2000rpm, and the stirring time of the high-speed stirring process is 0.5h-6h. Thus, the low-speed stirring plays a role in making the first coating material and the second coating material wrap the inner core; on the basis that the inner core surface has been covered by the first coating material and the second coating material, the high-speed stirring is performed so that the first coating material and the second coating material form a layered coating on the inner core surface. It is beneficial to wrap the surface of the inner core more evenly and completely, so that the prepared positive electrode material has a more uniform first coating layer or second coating layer, thereby making the interface between the positive electrode material and the solid electrolyte more stable.

[0091] In some embodiments, the rotation speed of the low-speed stirring process is 250rpm-300rpm, and the stirring time of the low-speed stirring process is 0.5h-1h; the rotation speed of the high-speed stirring process is 1000rpm-1200rpm, and the stirring time of the high-speed stirring process is 1h-2h.

[0092] In the third aspect of the present application, the present application proposes a method for preparing a positive electrode material, comprising: spraying a core precursor, wherein the spray-treated slurry comprises a coating material and a solvent, so as to obtain a preformed positive electrode material; and sintering the preformed positive electrode material to obtain the positive electrode material.

[0093] The coating material in the present application can be prepared into a slurry with good dispersibility and appropriate concentration, which is suitable for spraying treatment, so that a relatively uniform coating layer can be formed on the surface of the inner core and solidified by sintering treatment.

[0094] In some embodiments, the method further comprises: performing a first spraying treatment and a pre-sintering treatment on the core precursor in sequence, wherein the slurry of the first spraying treatment includes a second coating material; performing a second spraying treatment on the pre-sintered core precursor, wherein the slurry of the second spraying treatment includes the first coating material, so as to obtain the preformed positive electrode material. Thus, a multi-layer coating structure is formed on the core.

[0095] In some embodiments, the core precursor includes at least one of an MCN precursor, an NCA precursor, a lithium-rich manganese precursor, and an LFP precursor. a Co b Mn 1-a-b (ΟH)2, such as NCM622 precursor is Ni 0.6 Co 0.2Mn 0.2 (OH)2; NCA precursor: NCA precursor is Ni 0.8 Co 0.15 Al 0.05 (OH)2; the lithium-rich manganese precursor is Li c MnO is usually manganese oxide or manganese carbonate, such as MnCO3 or Mn3O4; LFP precursor is FePO4 or Fe2(SO4)3. The sources of the above precursors are stable, and cost control and quality control can be better performed.

[0096] In some embodiments, the pre-sintering temperature is 200°C-600°C, and the pre-sintering time is 1h-24h. Thus, within the pre-sintering temperature range, the first coating layer and the second coating layer formed by the first coating material and the second coating material have good adhesion and can form a film-like coating structure.

[0097] In some embodiments, the pre-sintering temperature is 400° C.-550° C., and the pre-sintering time is 4 h-12 h.

[0098] In some embodiments, the sintering temperature is 800° C.-1200° C., and the sintering time is 1 h-48 h. Within the sintering temperature range, the first coating material and the second coating material reach the compound reaction temperature to form the first coating layer and the second coating layer.

[0099] In some embodiments, the sintering temperature is 900° C.-1000° C., and the sintering time is 12 h-24 h.

[0100] In some embodiments, the solvent includes at least one of ethyl acetate, butyl butyrate, acetonitrile, acetone, toluene, xylene, ether, heptane, decane, hexane, n-heptane, chloroform, tetrahydrofuran, ethanol, butanol, N,N-dimethylacetamide, N,N-dimethylformamide, 2,2,2-trifluoro-N,N-dimethylformamide, and N-methylpyrrolidone. Thus, the solvent has good chemical stability with the first coating material and the second coating material, thereby reducing the influence of the solvent on the chemical properties of the first coating material and the second coating material.

[0101] In a fourth aspect of the present application, the present application proposes a battery, wherein the battery comprises the positive electrode material proposed in the present application.

[0102] In a fifth aspect of the present application, the present application proposes an electrical device, wherein the electrical device comprises the battery proposed in the present application.

[0103] The positive electrode material proposed in the present application can be prepared into a positive electrode sheet with an electronic conductive agent and an auxiliary agent through the following two methods. The positive electrode sheet, the electrolyte layer, and the negative electrode layer are sequentially stacked and packaged to form a battery.

[0104] Method 1: Wet preparation

[0105] S1: mixing the positive electrode material, the electronic conductive agent and the auxiliary agent in a preset ratio to form a slurry;

[0106] S2: coating the obtained slurry on the current collector according to a certain loading amount;

[0107] S3: Drying The current collector coated with the slurry is dried and then rolled to obtain a pole piece.

[0108] Method 2: Fibrillation preparation

[0109] S1: mixing the positive electrode material, the electronic conductive agent and the auxiliary agent in a preset ratio, applying shear force to the mixed powder to fiberize the auxiliary agent to obtain a blank;

[0110] S2: extruding or rolling the blank into a self-supporting film;

[0111] S3: The self-supporting film is loaded onto the current collector rolling between two rollers and rolled to form a pole piece.

[0112] Wherein, the electronic conductive agent includes at least one of graphite, hard carbon, soft carbon, carbon nanotubes, graphene, porous carbon, superconducting carbon black (Super P), acetylene black (Acetylene Black), and furnace black (Furnace Black).

[0113] The auxiliary agent includes at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), silicone rubber, styrene-butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), boronated polyethylene glycol, cellulose, cellulose ester, cellulose ether, nitrocellulose, carboxyalkyl cellulose, cellulose salt, sodium carboxymethyl cellulose and cellulose salt derivatives, polyacrylic acid (PAA), polyamide (PAI), polyvinyl alcohol (PVA), polyethylene imine (PEI), and polyimide (PI).

[0114] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0115] Example 1

[0116] The oxide solid electrolyte Li7La3Zr2O 12 As the first coating material, Li7La3Zr2O 12 With LiNi 0.8 Co 0.1 Mn 0.1 O2 is stirred at a mass ratio of 0.02:1, the protective gas is nitrogen, and the vacuum degree is -90kPa.

[0117] The low-speed stirring treatment was carried out at a rotation speed of 300 rpm for 1 hour; the high-speed stirring treatment was carried out at a rotation speed of 600 rpm for 24 hours.

[0118] Example 2

[0119] Li2MnCl4 was used as the first coating material, and 0.02 parts by mass of Li2MnCl4 and 1 part by mass of LiNi 0.8 Co 0.1 Mn 0.1 O2 is used for stirring treatment, the protective gas is nitrogen, and the vacuum degree is -90kPa.

[0120] The low-speed stirring treatment was carried out at a rotation speed of 300 rpm for 1 hour; the high-speed stirring treatment was carried out at a rotation speed of 550 rpm for 12 hours.

[0121] Li3InCl6 was used as the second coating material, and 0.02 mass parts of Li3InCl6 and Li7La3Zr2O 12 With LiNi 0.8 Co 0.1 Mn 0.1 The positive electrode material obtained after the O2 stirring treatment is stirred, the protective gas is nitrogen, and the vacuum degree is -90kPa.

[0122] The low-speed stirring treatment was carried out at a rotation speed of 300 rpm for 1 hour; the high-speed stirring treatment was carried out at a rotation speed of 600 rpm for 24 hours.

[0123] Example 3

[0124] Li3InCl6 was used as the first coating material, and 0.02 parts by mass of Li3InCl6 and 1 part by mass of LiNi 0.92 Co 0.06 Mn 0.02 O2 is used for stirring treatment, the protective gas is nitrogen, and the vacuum degree is -90kPa.

[0125] The low-speed stirring treatment was carried out at a rotation speed of 300 rpm for 1 hour; the high-speed stirring treatment was carried out at a rotation speed of 600 rpm for 24 hours.

[0126] Li6PS5Cl was used as the second coating material, and 0.02 mass parts of Li6PS5Cl, Li3InCl6 and LiNi 0.92 Co 0.06 Mn 0.02 The positive electrode material obtained after the O2 stirring treatment was stirred, and the low-speed stirring treatment was performed at a rotation speed of 300 rpm for 1 hour; the high-speed stirring treatment was performed at a rotation speed of 600 rpm for 12 hours.

[0127] Example 4

[0128] Li3InCl6 was mixed with anhydrous acetonitrile as solvent to prepare a first slurry, the concentration of which was about 1.5 g / L. 5 wt% of the first slurry was sprayed on the NCM811 precursor Ni 0.8 Co 0.1 Mn 0.1 The pre-sintering treatment was carried out on (OH)2 at 200℃ for 2h.

[0129] A second slurry is prepared by mixing Li6PS5Cl with anhydrous acetonitrile as a solvent. The concentration of the second slurry is about 1.5 g / L. 5 wt% of the second slurry by weight of the precursor is sprayed on the pre-sintered precursor and sintered at 800° C. for 12 hours to obtain a positive electrode material.

[0130] Example 5

[0131] Li3YCl6 was mixed with anhydrous acetonitrile as solvent to prepare a first slurry, the concentration of which was about 1.5 g / L, and 5 wt% of the first slurry was sprayed on the NCM811 precursor Ni 0.8 Co 0.1 Mn 0.1 The pre-sintering treatment was carried out on (OH)2 at 400℃ for 2h.

[0132] A second slurry is prepared by mixing Li6PS5Cl with anhydrous acetonitrile as a solvent. The concentration of the second slurry is about 1.5 g / L. 5 wt% of the second slurry by weight of the precursor is sprayed on the pre-sintered precursor and sintered at 800° C. for 12 hours to obtain a positive electrode material.

[0133] Comparative Example 1

[0134] The NCM811 precursor Ni without surface coating treatment 0.8 Co 0.1 Mn 0.1 (OH)2 is used as the positive electrode material.

[0135] Test method:

[0136] 1. First discharge specific capacity test

[0137] The method includes: performing charge and discharge cycles at a set current density using a constant current and constant voltage charge and discharge instrument (such as a Battery Testing System) at room temperature. The positive electrode material is made into a standard battery button or soft pack battery, and the counter electrode is lithium metal.

[0138] Test steps:

[0139] 1. Charge at a set current density (0.1C) to a set cut-off voltage of 4.25V.

[0140] 2. Discharge at the same current density (0.1C) until the set discharge cut-off voltage of 2.8V is reached.

[0141] 3. Record the specific capacity of the first discharge in mAh / g.

[0142] 2. First cycle coulomb efficiency test

[0143] Including: At room temperature, a constant current and constant voltage charge and discharge instrument is also used to measure the amount of electricity passing through the battery during the first charge and discharge process during the test.

[0144] Test steps:

[0145] 1. Charge to the set voltage and record the total charge (Q_charge).

[0146] 2. Discharge to the set cut-off voltage and record the total amount of discharge (Q_discharge).

[0147] 3. Calculate the first cycle coulombic efficiency: coulombic efficiency = (Q_discharge / Q_charge) × 100%.

[0148] 3.100-week capacity retention test

[0149] Including: charging and discharging the positive electrode material 100 times at room temperature under the same current density and voltage window.

[0150] Test steps:

[0151] 1. Perform 100 charge and discharge cycles on the battery, and periodically record the discharge capacity each time;

[0152] 2. Calculate the capacity retention after 100 cycles:

[0153] Capacity retention rate = (100th cycle discharge capacity / first discharge capacity) × 100%.

[0154] Test results: See Table 1.

[0155] Table 1

[0156]

[0157] From the test results, it can be seen that the preparation methods in Examples 1 to 3 and the preparation methods in Examples 4 and 5 can all produce the positive electrode materials proposed in this application. Compared with Comparative Example 1, the positive electrode materials prepared in Examples 1 to 5 have higher first-cycle coulombic efficiency and 100-cycle capacity retention rate, indicating that the interface between the positive electrode material and the solid electrolyte is relatively stable.

[0158] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0159] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0160] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0161] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode material, characterized in that: include: Kernel; A first coating layer, wherein the first coating layer includes a first coating material, and the first coating material includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer composite solid electrolyte; A second coating layer, wherein the second coating layer covers the inner core, the first coating layer covers the second coating layer, the second coating layer includes a second coating material, and the second coating material includes a halide solid electrolyte.

2. The positive electrode material according to claim 1, characterized in that The core includes at least one of lithium nickel cobalt manganese oxide, lithium iron manganese phosphate, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium rich manganese base, lithium nickel manganese oxide, and lithium vanadium phosphate.

3. The positive electrode material according to claim 1, characterized in that The core includes LiFePO4, LiFe x0 Mn y0 PO4, where x0+y0=1, Li3V2(PO4)3, LiVOPO4, LiNi x Co y Al z O2, where 0.7≤x≤0.85, 0.1≤y≤0.2, 0.05≤z≤0.1, LiNi 1-x’-y’ Mn x’ Co y’ O2, where 0.01≤x'≤0.95, 0.01≤y'≤0.95, LiCoO2, LiNiO2, LiMn2O4, LiNi 0.5 Mn 1.5 O. Li 1.2 Ni 0.2 Mn 0.6 O2、Li 1.2 Co 0.4 Mn 0.4 O2、x1Li2MnO3·(1-x1)LiNi 0.5 Mn 1.5 O4, where 0.05≤x1≤0.95, x2Li2MnO3·(1-x2)LiNi a2 Co b2 Mn c2 O2, wherein 0.05≤x2≤0.95, 0≤b2≤0.5, a2+b2+c2=1, at least one of the following.

4. The positive electrode material according to claim 1, characterized in that The room temperature ionic conductivity of the first coating material is ≥1E-4S / cm.

5. The positive electrode material according to claim 1, characterized in that The specific surface area of ​​the core is 0.5 m 2 / g-50m 2 / g.

6. The positive electrode material according to claim 1, characterized in that The D50 of the inner core is 0.5 μm-20 μm.

7. The positive electrode material according to claim 1, characterized in that The thickness of the first coating layer is 1 nm-50 nm.

8. The positive electrode material according to claim 1, characterized in that The thickness of the second coating layer is 1 nm-50 nm.

9. The positive electrode material according to claim 1, characterized in that The second coating material includes Li2MnCl4, Li2ZnCl4, Li2ZrOCl4, LiYbF4, LiAlF4, Li3YCl6, Li3InCl6, Li3InCl 5.5 F 0.5 、Li3TaCl6、Li 0.388 Ta 0.238 La 0.475 At least one of Cl3, Li6CoCl8.

10. The positive electrode material according to claim 1, characterized in that The thickness of the first coating layer is 2nm-10nm.

11. The positive electrode material according to claim 1, characterized in that The oxide solid electrolyte includes at least one of a sodium super ion conductor structure material, a perovskite structure material, an inverse perovskite structure material, a sulfur-substituted lithium ion conductor structure and a garnet structure material.

12. The positive electrode material according to claim 1, characterized in that The sulfide solid electrolyte includes Li2S-P2S5, Li 10 GeP2S 12 、Li3PS4、Li 6-x3 PS 5-x3 Cl 1+x3 , where 0≤x3≤0.

8.

13. The positive electrode material according to claim 1, characterized in that The molecular formula of the halide solid electrolyte is Li a4 (M b4 )X c4 X' d4 , wherein M includes at least one of Ga, Y, In, Mg, Sr, Sc, Sn, Pb, Ti, Zr, Hf, Nb, Ta, W, Fe, Ru, Al, and lanthanide metal elements, X includes at least one of halogen elements, X' includes at least one of halide ions, N ions, oxygen-containing anion groups, and pseudohalide anions, and the oxygen-containing anion groups include O 2- , S 2- , CN - 、CO3 2- PO4 3- 、P2O7 4- 、SO4 2- At least one of the pseudohalide anions includes SCN - PF 6- NH 2- , AlF 4- , or BF 4- At least one of the following, wherein 0.5≤a4≤5, 0.2≤b4≤4, c4+d4=a4+b4ε, wherein ε is the weighted average valence of the M element.

14. The positive electrode material according to claim 1, characterized in that The polymer composite solid electrolyte includes a polymer and a lithium salt, wherein the polymer includes at least one of polyethylene oxide, polyacrylate, polyvinylidene fluoride, hexafluoropropylene copolymer, polysiloxane, polyethylene glycol, sodium polystyrene sulfonate, polyvinyl cyanide, polysulfone, and polyether sulfone, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluoroantimonate, lithium bis(trifluoromethanesulfonate imide), lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium iodide, lithium magnesium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.

15. The positive electrode material according to claim 1, characterized in that The thickness of the first coating layer is 3nm-6nm.

16. The positive electrode material according to claim 1, characterized in that The oxide solid electrolyte includes Li 3x5 La 2 / 3-x5 TiO, 0≤x5≤0.16, Li 1+x6 Al x6 Ti 2-x6 (PO4)3, where 0≤x6≤0.5, Li 1+x7 Al x7 Ge 2-x7 (PO4)3, where 0≤x7≤0.5, Li7La3Zr2O 12 At least one of .

17. The positive electrode material according to claim 1, characterized in that The sulfide solid electrolyte includes at least one of Li2SP2S5 and Li6PS5Cl.

18. The positive electrode material according to claim 1, characterized in that The halide solid electrolyte includes Li2MnCl4, Li2ZnCl4, Li2ZrOCl4, LiYbF4, LiAlF4, Li3YCl6, Li3InCl6, Li3InCl 5.5 F 0.5 、Li3TaCl6、Li 0.388 Ta 0.238 La 0.475 At least one of Cl3, Li6CoCl8.

19. The positive electrode material according to claim 1, characterized in that The polymer composite solid electrolyte includes at least one of polyethylene oxide, hexafluoropropylene copolymer and polyvinyl cyanide.

20. A method for preparing the positive electrode material according to any one of claims 1 to 19, characterized in that: In a protective atmosphere, the core and the first coating material are subjected to a first stirring treatment to obtain a positive electrode material, wherein the first coating material comprises at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer composite solid electrolyte; The protective atmosphere includes at least one of nitrogen and an inert gas.

21. The method according to claim 20, characterized in that The method further comprises subjecting the inner core and the second coating material to a second stirring process before the first stirring process.

22. A method for preparing the positive electrode material according to any one of claims 1 to 19, characterized in that: The core precursor is subjected to a spraying treatment, wherein the slurry for the spraying treatment includes a coating material and a solvent, so as to obtain a preformed positive electrode material; The preformed positive electrode material is sintered to obtain the positive electrode material.

23. The method according to claim 22, characterized in that Further including: The core precursor is subjected to a first spraying treatment and a pre-sintering treatment in sequence, wherein the slurry of the first spraying treatment includes a second coating material; The core precursor that has undergone the pre-sintering treatment is subjected to a second spraying treatment, wherein the slurry of the second spraying treatment includes a first coating material, so as to obtain the preformed positive electrode material.

24. The method according to claim 23, characterized in that The temperature of the pre-sintering treatment is 200° C.-600° C., and the time of the pre-sintering treatment is 1 hour-24 hours.

25. The method according to claim 22, characterized in that The sintering temperature is 800° C.-1200° C., and the sintering time is 1 h-48 h.

26. The method according to claim 22, characterized in that The solvent includes at least one of ethyl acetate, butyl butyrate, acetonitrile, acetone, toluene, xylene, ether, heptane, decane, hexane, n-heptane, chloroform, tetrahydrofuran, ethanol, butanol, N,N-dimethylacetamide, N,N-dimethylformamide, 2,2,2-trifluoro-N,N-dimethylformamide, and N-methylpyrrolidone.

27. A battery, characterized in that: Comprising the positive electrode material according to claims 1-19.

28. An electrical device, characterized in that: Comprising the battery of claim 27.

Citation Information

Cited By

  • Composite positive electrode material and preparation method thereof

    CN120613386A

  • Composite cathode material and preparation method thereof

    CN120613386B

  • Nano single-crystal positive electrode material and preparation method thereof, solid-state battery and electric equipment

    CN120674481A

  • Halide sulfide double-layer coated positive electrode material as well as preparation method and application thereof

    CN120727807A

  • Halide sulfide double-layer coated cathode material, and preparation method and application thereof

    CN120727807B